2012
DOI: 10.32508/stdj.v15i2.1802
|View full text |Cite
|
Sign up to set email alerts
|

Studying on Growth of Strawberry (Fragaria Ananassa L.) Cell Suspension Cultures for Anthocyanin Production

Abstract: Cell suspension cultures were initated from calli derived from in vitro strawberry leaves on MS medium (Murashige and Skoog, 1962) supplemented with 30 g/l sucrose, 1.0 mg/l 2,4-D and 0.3 mg/l kinetin. There were many factors affected on cell suspension cultures growth (it was found that …). Cell suspension cultures grew better on MS medium with 30 g/l sucrose. 1 g (fresh weight) of cells in 20 ml of medium was the best initial inoculum cell density for cell suspension cultures to grow. A shaking speed of 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It was showed that cell density affected the growth of strawberry cell suspension (Fragaria ananassa L.), with a 1:20 (w/v) inoculum size being the most effective (17). However, unlike for Panax ginseng suspension cultures, cell growth was low at an inoculum size of 1:25 (w/v) and maximum cell growth was achieved with increasing inoculum size up to 1:10 (w/v).…”
Section: Effects Of Inoculum Size On the Proliferation Of E Asperula Cell Suspension Culturesmentioning
confidence: 99%
“…It was showed that cell density affected the growth of strawberry cell suspension (Fragaria ananassa L.), with a 1:20 (w/v) inoculum size being the most effective (17). However, unlike for Panax ginseng suspension cultures, cell growth was low at an inoculum size of 1:25 (w/v) and maximum cell growth was achieved with increasing inoculum size up to 1:10 (w/v).…”
Section: Effects Of Inoculum Size On the Proliferation Of E Asperula Cell Suspension Culturesmentioning
confidence: 99%